2014
DOI: 10.1042/bst20130256
|View full text |Cite
|
Sign up to set email alerts
|

Explorations of time and electrochemical potential: opportunities for fresh perspectives on signalling proteins

Abstract: Apoptosis is triggered by an accumulation of ROS (reactive oxygen species) produced by proteins of the mitochondrial respiratory chain. The levels of ROS are controlled by the activities of mitochondrial redox proteins such as glutaredoxin 2 that help to modulate the susceptibility of a cell to apoptosis. However, once downstream events have resulted in the release of cytochrome c to the cytosol, it is widely considered that cell death is inevitable. Cytochrome c may promote its own release from mitochondria t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…These results suggest that SeGrx1 may function to protect IOZCAS-Spex-II cells from CPT-induced oxidative stress, which confirms previous reports that Grx1 plays important roles in antioxidant defense in insects [26]. A similar result was reported that the levels of ROS are controlled by the activities of Grx2 in mitochondria, which can help to modulate the susceptibility of a cell to apoptosis [27]. Prior studies have noted the importance of Grx2 in mitochondrial redox status, when Grx2 knock-down resulted in increasing the sensitivity to cell death induced by doxorubicin/adriamycin and phenylarsin [28].…”
Section: Rnai Targeting Segrx1 Increased the Cytotoxicity Of Cpt In I...supporting
confidence: 91%
“…These results suggest that SeGrx1 may function to protect IOZCAS-Spex-II cells from CPT-induced oxidative stress, which confirms previous reports that Grx1 plays important roles in antioxidant defense in insects [26]. A similar result was reported that the levels of ROS are controlled by the activities of Grx2 in mitochondria, which can help to modulate the susceptibility of a cell to apoptosis [27]. Prior studies have noted the importance of Grx2 in mitochondrial redox status, when Grx2 knock-down resulted in increasing the sensitivity to cell death induced by doxorubicin/adriamycin and phenylarsin [28].…”
Section: Rnai Targeting Segrx1 Increased the Cytotoxicity Of Cpt In I...supporting
confidence: 91%
“…Through reversible oxidation and reduction of specific amino acids, often reactive cysteine residues, the mitochondrial “ROS signal” can thus target a wide variety of cellular processes. Redox-dependent signaling does not fall under the dogma of “oxidative stress” and may overall be the more important function of ROS in cells, tissues and organs [6].…”
Section: Introductionmentioning
confidence: 99%